Treponema pallidum Induces the Secretion of HDVSMC Inflammatory Cytokines to Promote the Migration and Adhesion of THP-1 Cells - Gao, Zheng-Xiang; Liu, Li-Li; Lin, Li-Rong; Tong, Man-Li; Liu, Fan; Yang, Tian-Ci (Frontiers in Cellular and Infection Microbiology, 2019)
The pathological features of syphilis, a disease caused by Treponema pallidum (T. pallidum), are characterized by vascular involvement with endarteritis and periarteritis. Little is known about the interactions of infiltrating immunocytes with human dermal vascular smooth muscle cells (HDVSMCs) in arterioles during the immunopathogenesis of syphilis. In the present study, we demonstrated that stimulation of HDVSMCs with T. pallidum resulted in the upregulated gene transcription and protein expression of interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1), and intercellular adhesion molecule-1 (ICAM-1) in a dose- and time-dependent manner. Moreover, the migration and adhesion of THP-1 cells to HDVSMCs were significantly suppressed by anti-MCP-1 and anti-ICAM-1 neutralizing antibodies, respectively. Further studies revealed that T. pallidum activated the NF-κB signaling pathway in HDVSMCs. Inhibition of NF-κB suppressed T. pallidum-induced IL-6, MCP-1, and ICAM-1 expression. In addition, the migration and adhesion of THP-1 cells to T. pallidum-treated HDVSMCs were significantly decreased by pretreatment with an NF-κB inhibitor. These findings demonstrate that T. pallidum induces the production of IL-6, MCP-1, and ICAM-1 in HDVSMCs and promotes the adherence and migration of THP-1 cells to HDVSMCs through the NF-κB signaling pathway, which may provide new insight into the pathogenesis of T. pallidum infection.